Introduction to the geological aspects of the planet Mars: implications for the possibility of human colonization - Silvestre, Gisllayne Roque (Cadernos de Astronomia, 2023)
This article was carried out from the compilation of pre-existing data in national and international literature and aims to analyze and discuss the geological conditions of the planet Mars and its potential for human colonization, bringing information from studies carried out mainly by probes sent to Mars, mapping in general and through in situ analysis of rocks and soils. Based on this, a comparative planetology was carried out between Earth and Mars, mainly in terms of the analysis of the geological structures present on both planets, to determine whether there was or could be water on Mars, an essential resource for the habitation of human beings. Also problematic such as the absence of a magnetic field, which can harm any living being due to the high solar radiation to which it is exposed; and the immense dust storms, which threaten to devastate structures and persist for weeks, make inhabiting Mars risky. It was possible to determine these main factors preventing the colonization of the Red Planet, analyzed as basic information by probes made by the American Space Agency (NASA) and the European Space Agency (ESA) and proposing ideas that may be able to make the colonization of Mars possible, such as creating a greenhouse effect, preventing the increase in dust storms and the placement of an artificial magnetosphere. The latter is shown to be the main solution to the problems addressed. And with the creation of a magnetosphere, it makes it possible for Mars to become more similar to Earth and more comfortable with regard to colonization, with the most advanced technology created by man so far and with further studies about the planet.